Chromium-Catalyzed Cross-Coupling Reactions by Selective Activation of Chemically Inert Aromatic C–O, C–N, and C–H Bonds - Cong, Xuefeng; Zeng, Xiaoming (Synlett, 2021)
Transition-metal-catalyzed cross-coupling has emerged as one of the most powerful and useful tools for the formation of C–C and C–heteroatom bonds. Given the shortage of resources of precious metals on Earth, the use of Earth-abundant metals as catalysts in developing cost-effective strategies for cross-coupling is a current trend in synthetic chemistry. Compared with the achievements made using first-row nickel, iron, cobalt, and even manganese catalysts, the group 6 metal chromium has rarely been used to promote cross-coupling. This perspective covers recent advances in chromium-catalyzed cross-coupling reactions in transformations of chemically inert C(aryl)–O, C(aryl)–N, and C(aryl)–H bonds, offering selective strategies for molecule construction. The ability of low-valent Cr with a high-spin state to participate in two-electron oxidative addition is highlighted; this is different from the mechanism involving single-electron transfer that is usually assigned to chromium-mediated transformations.1 Introduction2 Chromium-Catalyzed Kumada Coupling of Nonactivated C(aryl)–O and C(aryl)–N Bonds3 Chromium-Catalyzed Reductive Cross-Coupling of Two Nonactivated C(aryl)–Heteroatom Bonds4 Chromium-Catalyzed Functionalization of Nonactivated C(aryl)–H Bonds5 Conclusions and Outlook
Keywords: chromium catalysis; homogeneous catalysis; cross-coupling